Influence of lateral excursion on vestibular cervical dental abfraction. - Palomino-Gómez, Sandra P; Jeremias, Fabiano; Finoti, Livia S; Paredes-Coz, Gerson; Raveli, Dirceu B (My University, 2011)
A study was performed to evaluate the influence of mandibular lateral excursion, group function and canine guidance on vestibular cervical dental abfraction (VCDA). Thirty-six individuals of both sexes, aged 20 to 45 years, with full natural dentition with at least one tooth with VCDA were selected at the San Marcos University Clinic. We evaluated number of teeth with VCDA per side (left and right), tooth type and lateral excursive movement (canine guidance or group function) affecting it. The results showed no statistical difference (p > 0.05). The tooth type most often showing VCDA was the first lower premolar, with 30.8% on the right side and 36.4% on the left. Moderate positive correlation was found between age and VCDA (R = 0.40). It is concluded that group function during lateral excursion may contribute to presence of VCDA.
Keywords: adult; female; human; male; mandible; middle aged; physiology; tooth disease; tooth occlusion; Adult; Dental Occlusion; Female; Humans; Male; Mandible; Middle Aged; Tooth Wear; Young Adult